Synchronous Supraglottic and Esophageal Squamous Cell Carcinomas Treated with a Monoisocentric Hybrid Intensity-Modulated Radiation Technique - Barney, Christian L.; Zamora, Pedro; Ewing, Ashlee; Old, Matthew; Chakravarti, Arnab; Bhatt, Aashish (Frontiers in Oncology, 2018)
Risk factors for squamous cell carcinomas (SCC) of the head and neck (HN) and esophagus are similar. As such, synchronous primary tumors in these areas are not entirely uncommon. Definitive chemoradiation (CRT) is standard care for locally advanced HN-SCC and is a preferred option for inoperable esophageal SCC. Simultaneous treatment of both primaries with CRT can present technical challenges. We report a case of synchronous supraglottic and esophageal SCC primary tumors, highlighting treatment with a monoisocentric hybrid radiation technique and normal tissue toxicity considerations.